Lisina e metionina na dieta de vacas de alta produção mantidas em pastagens de azevém (Lolium multiflorum Lam.) e suplementadas com concentrado de baixo teor proteico - Lima, Luís Otávio da Costa de (2017)
Current research looked into the effects of supplementing essential amino acids L-lysine and DL-methionine to lactating dairy cows, grazing annual ryegrass and receiving a low protein concentrate meal. Twenty Holstein cows were managed in a 2x2 crossover experimental design, with two treatments and two periods. Cows received the same diet in both treatments, except for the inclusion of 20g lysine and 60g methionine in one treatment. This aimed at supplying 6.92% and 2.34% of the metabolizable protein in lysine and methionine, respectively, as suggested by the Cornell Net Carbohydrate and Protein System (CNCPS). No significant differences were found in milk (36,19 vs. 35,97kg), total crude protein (1,14 vs. 1,15kg) and lactose (1,62 vs. 1,66kg) yields, casein content (2,55 vs. 2,55%), somatic cell count (309 vs. 363cél.mL-1), milk urea nitrogen (12,40 vs. 12,15mg.dL-1), and blood urea (25,01 vs. 25,09mg.dL-1) for the control and the amino acid supplemented treatments, respectively. The amino acid supplemented treatment presented a lower milk fat content (3,58 vs. 3,39%), but no differences yield (1,29 vs. 1,21kg), which led to the same 4% milk fat corrected milk yield (33,8 vs. 32,6kg). The lower milk fat content resulted in a lower total milk solids content (12,56 vs. 12,26%) in the amino acid supplemented treatment, in spite of this treatment presenting similar crude protein (3,17 vs. 3,20%) and lactose (4,48 vs. 4,61%) contents. Animals receiving the amino acid supplementation also presented lower creatinine blood (0,74 vs. 0,89mg.dL-1) suggesting a lower muscle tissue mobilization, in spite of their similar urine urea nitrogen test (264,15 vs. 351,30 mg.dL-1) and urine creatinine (42,46 vs. 38,04mg.dL-1). Rumen-protected lysine and methionine supplementation did not affect milk yield but did affect milk composition and reduced serum creatinine.